MO955RENAL TRANSPLANTATION IN PATIENTS WITH LOW URINARY TRACT ABNORMALITIES. (29th May 2021) - Ladhari, Narjes; Awatef, Azzabi; Wissal, Sahtout; Yosra, Guedri; Sanda, Mrabet; Narjes, Ben Aicha; Dorsaf, Zellama; Abdellatif, Achour
Abstract: Background and Aims: Kidney transplantation is the only curative treatment for chronic kidney failure that allows to restaure a normal quality of life for patients. In case of abnormalities of the lower urinary tract, there is a risk of recurrence of renal failure due to urodynamic disturbances. The objective of our study is to analyze the profile of transplanted patients with urodynamic abnormalities and to study their impact on the graft. Method: Our study was conducted within our Nephrology Department, including renal transplant patients during the period from 2007 to 2020 and who underwent a pre-transplant urodynamic evaluation. Patients with vesical or sphincteral abnormalities were selected, their demographic characteristics, graft survival and infectious complications compared to patients without vesico-sphincteral abnormalities were studied. Results: Of 209 kidney transplant patients during the period 2007-2020, 54 had undergone a pre-transplant urodynamic assay, which resulted in 32 patients having an abnormality: 12 cases of vesical hypertonia or hypotonia, 12 cases of sphincteral hypertonia and 9 patients had vesico-sphincteral dyssynergy. In this group with vesical abnormalities, the average age was 24 years, with extremes of 7 and 49 years, 19 were male versus 13 females. Initial nephropathy was tubulointerstitial in 75% of cases with reflux nephropathy in 17 patients. Comparing this group (G1) to the group of patients with no vesico-sphincteral abnormalities (G2), there was more graft reflux 34.4% in G1 compared to 18.2% in G2 (p= 0.16), more urological complications (p=0.2), more urinary tract infections, 0.55 episodes per patient per year in G1 versus 0.98 in G2 (p=0.21). For the graft function, there was no statistically significant difference between the 5-year creatinine post-transplant averages. Conclusion: Vesico-sphincteral abnormalities are frequently found in young patients with pre-transplant NIC, they are not responsible for more post-transplant complications or significant graft failure